The Use of Detached Leaf Inoculation for Selecting Cercospora kikuchii Resistance in Soybean Genotypes - Kashiwa, Takeshi; Lavilla, Miguel Angel; Diaz Paleo, Antonio Horacio; Ivancovich, Antonio Juan Gerardo; Yamanaka, Naoki (The American Phytopathological Society (APS), 2022)
Cercospora leaf blight (CLB) causes extensive losses in soybean production in worldwide, including major soybean-producing countries such as Argentina. Cercospora kikuchii, C. cf. sigesbeckiae, C. cf. flagellaris, and C. cf. nicotianae are identified as pathogens of CLB. Soybean resistance against CLB is still unknown. Also, chemical control for CLB is losing effectiveness because of fungicide resistance of pathogens such as C. kikuchii. We urgently need to breed a CLB-resistant cultivar. Unfortunately, efficient methods for the screening of a resistant soybean genotype have not yet been established. In this study, we designed a new, high-throughput inoculation method for identifying resistance against one of the CLB pathogens, C. kikuchii. We used liquid-cultured mycelia of the pathogen C. kikuchii on detached soybean leaves. Lesions on soybean leaflets appeared 9 days postinoculation by this method. We used this method to select four C. kikuchii-resistant genotypes from 80 genotypes in the World Soybean Core Collection. The high-throughput screening method developed in this study can contribute to the research about C. kikuchii resistance by facilitating identification of resistant varieties.